VD_FINDINFO AVS 37/20 - 35/2021 vom 13. Juli 2021 - VD Tribunal cantonal (2021)
AFFILIATION AUX CAISSES, ACTIVITÉ LUCRATIVE INDÉPENDANTE, VOYAGEUR DE COMMERCE | 3 LAVS, 5 LAVS, 9 LAVS, 10 LPGA, 12 LPGA, 6 RAVS